2021
DOI: 10.21037/qims-19-761
|View full text |Cite
|
Sign up to set email alerts
|

Time-efficient and contrast-free magnetic resonance imaging approach to the diagnosis of deep vein thrombosis on black-blood gradient-echo sequence: a pilot study

Abstract: Background: Black-blood thrombus imaging (BTI) has shown to be advantageous for the diagnosis of deep vein thrombosis (DVT). However, previous techniques using fast spin echo have a high specific absorption rate. As DANTE (delay alternating with nutation for tailored excitation) black-blood preparation can suppress blood flows over a broad range of velocities, we hypothesized that a DANTE black-blood preparation combined with a fast low-angle shot (FLASH) gradient-echo readout-DANTE-FLASH could be used to diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Previous studies have confirmed the high sensitivity of MRBTI for investigating thrombi in the context of acute ischemic stroke, 3 myocardial infarction, 4 and deep venous thrombosis. 5,6 In the present study, the accuracy and superiority of MRBTI for confirming CVT in the chronic stage was demonstrated for the first time.…”
Section: Introductionsupporting
confidence: 57%
“…Previous studies have confirmed the high sensitivity of MRBTI for investigating thrombi in the context of acute ischemic stroke, 3 myocardial infarction, 4 and deep venous thrombosis. 5,6 In the present study, the accuracy and superiority of MRBTI for confirming CVT in the chronic stage was demonstrated for the first time.…”
Section: Introductionsupporting
confidence: 57%
“…Conversely, Palanisamy et al supported the effectiveness and convenience of Wells predictive score for identifying DVT in the general population well in time to commence anticoagulation without delay [ 94 ]. Latest studies have shown that the new imaging technique, Delay Alternating with Nutation for Tailored Excitation black-blood preparation combined with a Fast Low-Angle Shot (DANTE-FLASH) produced superior picture quality and detected thrombi far more accurately than MRDTI and ultrasound, recommending it as a practical, time-efficient, and safe option to diagnose DVT [ 95 ].…”
Section: Reviewmentioning
confidence: 99%